Caries disparities among Medicaid‐enrolled young children from pediatric primary care settings. (2nd November 2020) - Selvaraj, David; Curtan, Shelley; Copeland, Tashyana; McNamee, Erin; Debelnogich, Jelena; Kula, Taylor; Momotaz, Hasina; Nelson, Suchitra
Abstract: Objectives: The objectives of this study are to determine the overall and racial differences in the extent of caries experience and to examine the association between child and parent/caregiver characteristics and caries among 3–6‐year‐old Medicaid‐enrolled children. Methods: This study reports baseline cross‐sectional data from a larger pragmatic clinical trial in pediatric primary care practices. Child‐level clinical dental exams included decayed and filled teeth (dft) using ICDAS criteria and parent/caregiver questionnaire collected information on socio‐demographics, child oral health behaviors, oral health related quality of life (OHQoL), and food environment. Results: A total of 1, 024 parent/caregiver‐child dyads participated in the study. The overall caries experience (dft) was 49 percent and untreated decay was 42 percent. Children who were Black had 1.3 and 1.2 times significantly higher frequency of untreated primary decay and caries experience compared to non‐Black children. An overall logistic regression model predicted that race, increased age, receiving dental care in the past 12 months for a cavity/toothache, and lower caregiver OHQoL was significantly associated with increased odds of the child having caries. Non‐Black caregivers with less education, whose child was older, and lower child OHQoL had increased odds of having a child with caries, but these same variables were not predictive for the Black children. Conclusions: Racial disparities exist with respect to caries experience and untreated decay within a Medicaid‐enrolled population of young children attending well‐child visits. Pediatric primary care offices are well‐positioned to provide dental surveillance and preventive care and could play an important role in decreasing oral health inequities.